2019
DOI: 10.3389/fgene.2019.00435
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Biogenesis as a Way for Active Longevity: Interaction Between the Nrf2 and PGC-1α Signaling Pathways

Abstract: Aging is a general degenerative process related to deterioration of cell functions in the entire organism. Mitochondria, which play a key role in energy homeostasis and metabolism of reactive oxygen species (ROS), require lifetime control and constant renewal. This explains recently peaked interest in the processes of mitochondrial biogenesis and mitophagy. The principal event of mitochondrial metabolism is regulation of mitochondrial DNA (mtDNA) transcription and translation, which is a complex coordinated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
347
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 475 publications
(360 citation statements)
references
References 187 publications
(212 reference statements)
10
347
2
1
Order By: Relevance
“…PPARγ coactivator-1α (PGC-1α) acts as a key factor and connects several regulatory cascades involved in the control of mitochondrial metabolism. PGC-1α knockout dysregulates the Nrf2-dependent mitochondrial biogenesis through the PGC-1α/p38/GSK3β/Nrf2 cascade (Navarro et al, 2017;Gureev et al, 2019). In the course of research whether and how naringenin (NGN) would be able to prevent the mitochondria-related bioenergetics and redox dysfunctions induced by methylglyoxal (MG) in the human neuroblastoma SH-SY5Y cells, researchers found that NGN caused mitochondrial protection by an Nrf2/GSH-dependent manner (de Oliveira et al, 2019).…”
Section: Nadph Regenerationmentioning
confidence: 99%
“…PPARγ coactivator-1α (PGC-1α) acts as a key factor and connects several regulatory cascades involved in the control of mitochondrial metabolism. PGC-1α knockout dysregulates the Nrf2-dependent mitochondrial biogenesis through the PGC-1α/p38/GSK3β/Nrf2 cascade (Navarro et al, 2017;Gureev et al, 2019). In the course of research whether and how naringenin (NGN) would be able to prevent the mitochondria-related bioenergetics and redox dysfunctions induced by methylglyoxal (MG) in the human neuroblastoma SH-SY5Y cells, researchers found that NGN caused mitochondrial protection by an Nrf2/GSH-dependent manner (de Oliveira et al, 2019).…”
Section: Nadph Regenerationmentioning
confidence: 99%
“…Table 3. Principal functions of enzymes encoded by Nrf2 target genes and involved in the antioxidant defence [186,197,[202][203][204].…”
Section: Transcription Factor Nrf2mentioning
confidence: 99%
“…Importantly, Nrf2 was shown to restrict/prevent iron-or heme-mediated oxidative stress by affecting the expression of the FPN1, ferritin and HO-1 genes [250]. Regulation of the aforementioned antioxidants, NADPH-synthesizing enzymes, as well as others stress-response proteins are clearly shown to provide protection against oxidative and inflammatory damages [197,203,204,251]. Accumulating evidence clearly shows that Nrf2 can also regulate many important biological processes, including cell proliferation and differentiation, inflammation, autophagy, apoptosis, mitochondrial function or biogenesis as well as several metabolic pathways involved in iron/heme, glucose, glutamine, lipid, NADPH and pentose phosphate metabolism (for review and references, see Reference [198]).…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 99%
See 1 more Smart Citation
“…35 The components of mitochondria are engulfed by autophagosomes and degraded by lysosomes. 37 It is increased by nuclear respiratory factors (NRF1 and NRF2), estrogen-related receptors (ERR-α, ERR-β, and ERR-γ), and peroxisome proliferator-activated receptor gamma (PPAR-γ) and PPAR-γ coactivator 1-alpha (PGC-1α). Mitophagy is regulated by Pink1 and parkin.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%